2004
DOI: 10.1016/s0021-9673(04)01213-0
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction for pesticide multiresidue analysis in honey: determination by gas chromatography with electron-capture and mass spectrometry detection

Abstract: An analytical procedure using supercritical fluid extraction (SFE) and capillary gas chromatography with electron-capture detection was developed to determine simultaneously residues of different pesticides (organochlorine, organophosphorus, organonitrogen and pyrethroid) in honey samples. Fortification experiments were conducted to test conventional extraction (liquid-liquid) and optimize the extraction procedure in SFE by varying the CO2-modifier, temperature, extraction time and pressure. Best efficiency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 0 publications
0
59
0
8
Order By: Relevance
“…These studies, however, usually focused on the analysis of very few compounds, often belonging to one or two pesticide families at the most, such as organochlorine or organophosphorous residues. As demands of pesticide analysis started to be more motivated accordingly similar agrarian uses rather than similar physico-chemical properties of chemicals, multi-analyte determinations have appeared since the end of nineties, covering several classes of pesticides [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, usually focused on the analysis of very few compounds, often belonging to one or two pesticide families at the most, such as organochlorine or organophosphorous residues. As demands of pesticide analysis started to be more motivated accordingly similar agrarian uses rather than similar physico-chemical properties of chemicals, multi-analyte determinations have appeared since the end of nineties, covering several classes of pesticides [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Argauer et al developed a method to isolate ten pyrethroids from ground meat using SF-CO2 [382]. Rissato et al reported a SFE method that combined extraction and Florisil ® clean up of pyrethroids residues from honey samples [383]. More recently solid-phase microextraction (SPME), MSPD and QuEChERS have been used in the analysis of pyrethroids.…”
Section: Pyrethroidsmentioning
confidence: 99%
“…A number of supercritical fluid extraction SFE methods have been developed as alternatives to conventional liquid extraction methods for determining pesticide residues in foods, such as vegetables and fruits 2 -10 , cereals 11 -16 , eggs 17 , 18 , meat 19 , oil 20 , baby food 21 , and honey 22 . The main advantages of SFE are that it can lead to less solvent use and that it can be automated, reducing labor costs.…”
Section: Introductionmentioning
confidence: 99%